Aprendizagem criativa-colaborativa e liderança musical: princípios e práticas - Daniel Augusto Oliveira Machado (2016)
This research theme is the investigation of possible links between creative-collaborative learning and musical leadership. It aims to analyze and connect these topics from literature review and analysis of data collected in collective musical creation processes with 37 students from the School of Music of the Federal University of Minas Gerais, at Creation Laboratory I discipline, during the 1st half of 2015. The goal is to understand how such students built their knowledge and musical, intrapersonal and interpersonal skills during the classes, and the meanings and values assigned to them, and to investigate current conflicts throughout the process, impacts on their musical practices and expectations about Creation Laboratory I classes in EMUFMG. In this qualitative research, questionnaires and focus groups were used as data collection techniques. Impacts on listening, creativity and musical preferences of students were found as a result of Creation Laboratory lessons. The research suggests, finally, that the assessment of knowledge and skills related to collective musical creation processes can be interpreted as a way for the connection between creative-collaborative learning and musical leadership.